Detection and comparison of specific hemin binding by Porphyromonas gingivalis and Prevotella intermedia. - Tompkins, G R (1997)
A radioligand assay was designed to detect and compare specific hemin binding by the periodontal anaerobic black-pigmenting bacteria (BPB) Porphyromonas gingivalis and Prevotella intermedia. The assay included physiological concentrations of the hemin-binding protein rabbit serum albumin (RSA) to prevent self-aggregation and nonspecific interaction of hemin with cellular components. Under these conditions, heme-starved P. intermedia cells (two strains) expressed a single binding site species (4,100 to 4,600 sites/cell) with a dissociation constant (Kd) of 1.0 x 10(-9) M. Heme-starved P. gingivalis cells (two strains) expressed two binding site species; the higher-affinity site (1,000 to 1,500 sites/cell) displayed a Kd of between 3.6 x 10(-11) and 9.6 x 10(-11) M, whereas the estimated Kd of the lower-affinity site (1.9 x 10(5) to 6.3 x 10(5) sites/cell) ranged between 2.6 x 10(-7) and 6.5 x 10(-8) M. Specific binding was greatly diminished in heme-replete cells of either BPB species and was not displayed by iron-replete Escherichia coli cells, which bound as much hemin in the absence of RSA as did P. intermedia. Hemin binding by BPB was reduced following treatment with protein-modifying agents (heat, pronase, and N-bromosuccinimide) and was blocked by protoporphyrin IX and hemoglobin but not by Congo red. Hemopexin also inhibited bacterial hemin binding. These findings indicate that both P. gingivalis and P. intermedia express heme-repressible proteinaceous hemin-binding sites with affinities intermediate between those of serum albumin and hemopexin. P. gingivalis exhibited a 10-fold-greater specific binding affinity and greater heme storage capacity than did P. intermedia, suggesting that the former would be ecologically advantaged with respect to heme acquisition.